2019
DOI: 10.1111/cea.13345
|View full text |Cite
|
Sign up to set email alerts
|

Pru p 7 sensitization is a predominant cause of severe, cypress pollen‐associated peach allergy

Abstract: Background: Peach is a common elicitor of food allergic reactions. Peach-induced immediate reactions may occur as benign pollen-food syndromes, usually due to birch pollen-related PR-10 cross-reactivity in temperate climates, and as potentially severe primary food allergies, predominantly related to nsLTP Pru p 3 in Mediterranean regions. The newly described peach allergen Pru p 7 has gained recent attention as a potential peach allergy severity marker. Sensitization to Pru p 7 and its allergenic homologues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 48 publications
(74 reference statements)
3
71
3
3
Order By: Relevance
“…An important association was recently reported between cypress pollinosis, levels of pollen exposure, and peach allergy due to sensitization to peamaclein (Pru p 7) in a French population. The authors reported that cypress pollen extract completely outcompeted IgE binding to Pru p 7 [6]. In accordance with previous studies, monosensitization to cypress pollen was exceptional in our population [7].…”
supporting
confidence: 92%
“…An important association was recently reported between cypress pollinosis, levels of pollen exposure, and peach allergy due to sensitization to peamaclein (Pru p 7) in a French population. The authors reported that cypress pollen extract completely outcompeted IgE binding to Pru p 7 [6]. In accordance with previous studies, monosensitization to cypress pollen was exceptional in our population [7].…”
supporting
confidence: 92%
“…Participating centers were left free to employ the commercial SPT preparations that they used in their routine activity; producers included Allergopharma (Reinbeck, Germany), ALK (Horsholm, Denmark), and Lofarma (Milano, Italy). Skin tests were carried out following established methods [16]; readings were taken after 15 1© 2020 Esmon Publicidad doi: 10.18176/jiaci.0542 activity. The ALK extract is known to lack labile allergens (such as PR-10 and profilin) and to contain stable allergens such as LTP [17] and peamaclein [3].…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…Other foods have been reported to be potential inducers of allergic reactions in patients hypersensitive to this family of allergens, including Japanese apricot [12], orange [13], and pomegranate [14], the names of these allergens being Pru m 7, Cit s 7, and Pun g 7, respectively. Further, clinical reactivity against apple, melon, watermelon, and strawberry [2], as well as to exotic fruits, kiwi, tomato, fig, carrot, grapes, coconut, and celeriac [15] has been reported in Pru p 7-hypersensitive patients making GRP a potential novel plant-food panallergen.…”
Section: Introductionmentioning
confidence: 99%
“…BP14 from cypress pollen, Pru p 7 from peach, and Pun g 7 from pomegranate are some representative GRP molecules. [214][215][216][217] Kiwi Among 59 people in Sweden with peanut allergy, 39% also reported symptoms to kiwi, likely elicited by cross-reactivity between the 11S and 7S globulins present in both kiwi and peanut, and cosensitization to the kiwi 2S albumin Act d 13. 218 Additional reactivities to nuts and legumes other than peanuts were also reported.…”
Section: Rosaceae Fruitsmentioning
confidence: 99%